Mindfulness, preferences and well-being: Mindfulness predicts adolescents' field behaviour - Katharina Lima de Miranda (Kiel Institute for the World Economy (IfW), 2019)
Mindfulness could influence economic and health related behaviour by bringing about increased and unbiased attention to the present moment, for example to a decision making process. This study explores the relationship between mindfulness and economic preferences, and consequently well-being, of adolescents. Comprehensive data of 525 German secondary school students were elicited and show no evidence for a strong linear or non-linear correlation between mindfulness and economic preferences. However, both mindfulness and preferences have explanatory power for adolescents' field behaviour and thus contribute to explaining variation in behaviour that may translate into serious health and economic consequences. In this regard, my findings indicate that the two concepts play rather complementary than substitutable roles, which implies that an integration of economic preferences and personality traits such as mindfulness may improve the analysis of potential sources of variation in life outcomes. As mindfulness reflects on a healthier lifestyle (less smoking and smaller BMI) and higher life satisfaction, the findings furthermore point into the direction that the development of mindfulness skills might help students to grow social-emotional capacities and increase physical and psychological well-being.
Keywords: C93; D81; D90; I12; I20; 330; time preference; risk preferences; mindfulness; personality; experiments with adolescents; subjective well-being